Sistem Pewarisan dan Keberlanjutan Pengelolaan Usaha Tambak Garam Desa Genengmulyo, Kecamatan Juwana - Rohana, Siti; Juhadi, Juhadi (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2019)
The research problems are include (1) How is the cooperative model type talking stick which is helped multimedia quiz creator to improve the senior high school students’ folklore attentive skill. (2) how is the principles of cooperative model type talking stick development which is helped by multimedia quiz creator to improve the senior high school students’ folklore attentive skill. This research uses research and development design (R&D), this research developes model which have been exist that is cooperative model type talking stick into cooperative model type talking stick which is helped by multimedia quiz creator. The results of the researches are : (1) the teacher and students’ need toward to cooperative model type talking stick which is helped by multimedia quiz creator. (2) cooperative model type talking stick priciples are (a) innovative learning strategy, (b) innovative learning media, (c) assessment. Masalah penelitian meliputi (1) bagaimanakah kebutuhan model kooperatif tipe tongkat bicara berbantuan multimedia kuis kreator untuk meningkatkan keterampilan menyimak cerita rakyat peserta didik SMA; (2) bagaimanakah prinsip-prinsip model kooperatif tipe tongkat bicara berbantuan multimedia kuis kreator untuk meningkatkan keterampilan menyimak cerita rakyat peserta didik SMA. Penelitian ini menggunakan desain Research and Development (R&D). Penelitian ini mengembangkan model yang sudah ada yaitu model kooperatif tipe tongkat bicara menjadi model kooperatif tipe tongkat bicara berbantuan multimedia kuis kreator untuk meningkatkan keterampilan menyimak cerita rakyat peserta didik SMA.Hasil penelitian ini adalah: (1) kebutuhan guru dan peserta didik terhadap model kooperatif tipe tongkat bicara berbantuan multimedia kuis kreator (2) prinsip-prinsip model kooperatif tipe tongkat bicara berbantuan multimedia kuis kreator, yaitu: (a) strategi pembelajaran inovatif, (b) media pembelajaran inovatif, (c) penilaian.